Bionanoparticle‐Based Delivery in Antihypertensive Vaccine Mediates DC Activation through Lipid‐Raft Reorganization. (4th March 2020) - Hu, Xiajun; Chen, Xiao; Shi, Xiaoli; Gao, Jingwei; Ao, Zhuo; Li, Nan; Yuan, Jinghe; Fang, Xiaohong; Qiu, Zhihua; Zhou, Zihua; Liao, Yuhua; Han, Dong
Abstract: Bionanoparticles (BNPs) are widely used as vaccine carriers. Compared with classic protein carriers, BNPs exhibit nanostructures that enable them to interaction with biointerface‐like cell membrane or membrane domains. An antihypertensive vaccine ATR‐NP is produced based on a virus‐like particle (VLP) Qβ carrier. Qβ shows great delivery efficiency and immunogenicity to antigen‐presenting cells (APCs) such as dendritic cells (DCs), and DC activation induced by ATR‐NP is highly dependent on membrane lipid rafts. Further studies reveal that ATR‐NP exhibits tight affinity to rafts, and interface effects between them prompt membrane phase separation and raft accumulation through NP‐induced membrane curvature change. Lipid rafts are accumulated and expanded together with a decline of their diffusion in membrane, which benefits signaling protein Src partition in rafts. The heterogeneous protein partition implies functional centralization for stronger signal transduction. In conclusion, targeting and reorganizing membrane domains such as lipid rafts suggests BNPs could be used as vaccine carriers and is a potent strategy for vaccine and other immunological agent design. Abstract : Bionanoparticles (BNPs) exhibit nanostructures with special physiochemical characteristics, and their biosurfaces allow size‐compatible interactions with membrane domains such as lipid rafts. Due to their size effect, BNPs induce membrane bending when contacting with cells; the increased membrane curvature promotes lipid phase separation and raft accumulation. The expanded raft domains become larger platforms that immediately transmit signals for cell functions.